2013
DOI: 10.1371/journal.pone.0063479
|View full text |Cite
|
Sign up to set email alerts
|

Risk Profiles and Antithrombotic Treatment of Patients Newly Diagnosed with Atrial Fibrillation at Risk of Stroke: Perspectives from the International, Observational, Prospective GARFIELD Registry

Abstract: BackgroundLimited data are available on the characteristics, clinical management, and outcomes of patients with atrial fibrillation at risk of stroke, from a worldwide perspective. The aim of this study was to describe the baseline characteristics and initial therapeutic management of patients with non-valvular atrial fibrillation across the spectrum of sites at which these patients are treated.Methods and FindingsThe Global Anticoagulant Registry in the FIELD (GARFIELD) is an observational study of patients n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

18
297
6
31

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 412 publications
(352 citation statements)
references
References 26 publications
18
297
6
31
Order By: Relevance
“…Anticoagulation use was highest among those with MS/MV. Anticoagulation use was comparable in our cohort of patients to other contemporary registries in which anticoagulation use has ranged from 70% to 80% 20, 21, 22, 23. Notably, there were 6 patients in which DOAC use was reported in the setting of MS/MV.…”
Section: Discussionsupporting
confidence: 64%
“…Anticoagulation use was highest among those with MS/MV. Anticoagulation use was comparable in our cohort of patients to other contemporary registries in which anticoagulation use has ranged from 70% to 80% 20, 21, 22, 23. Notably, there were 6 patients in which DOAC use was reported in the setting of MS/MV.…”
Section: Discussionsupporting
confidence: 64%
“…Similarly, the Frailty, Stroke Risk and Bleeding Risk on Anticoagulation in the Elderly With Atrial Fibrillation (FRAIL‐AF) study showed that patients classified as non‐to‐moderately frail using the Clinical Frailty Scale (CFS) were 3.4‐fold ( P <0.0001) more likely to receive anticoagulation therapy than patients classified as severely frail (CFS ≥7) 6. Studies have shown cognitive dysfunction or dementia, perceived fall risk and advancing age, each of which are included in the Johns Hopkins Claims‐based Frailty Indicator, to be associated with a significant reduction in the odds of anticoagulation use in NVAF patients 20, 21. Furthermore, some clinicians have supported utilizing certain OACs, or reduced doses of OACs in various clinical scenarios often associated with a frail state (eg, >75 years old, renal impairment) 7.…”
Section: Discussionmentioning
confidence: 99%
“…В зарубежных регистрах GARFIELD [7], PREFER [8] и международном наблюдательном исследовании XANTUS [9] также наблюдались пациенты с высоким риском тромбо-эмболических осложнений. В сравнении с нашими дан-ными и результатами РЕКВАЗА, несколько реже встреча-лись такие факторы риска, как АГ, застойная ХСН и пере-несенный инфаркт миокарда.…”
Section: результаты и обсуждениеunclassified
“…), что близко к данным наблюдательного проекта XANTUS (44%) [9]. По материа-лам зарубежных регистров GARFIELD [7] Средний балл по CHADS 2 Примечание. ТКЦ -Тюменский кардиологический центр (собственные данные); «-» -нет данных.…”
Section: результаты и обсуждениеunclassified